EVALUATING INITIATIVE TO REDUCE AVOIDABLE HOSPITALIZATIONS AMONG NURSING FACILITY RESIDENTS: METHODS OVERVIEW. (11th November 2018) - Feng, Z; Segelman, M; Li, Q; Vreeland, E; Ingber, M
Abstract: RTI is conducting a comprehensive multiyear evaluation using a mix of quantitative and qualitative methods to assess the effectiveness of the new payment model in reducing avoidable hospitalizations, improving health outcomes, and reducing spending. This presentation will describe the approaches to selecting comparison groups and evaluating the Initiative effect, to address challenges related to the Initiative design. For each Initiative state, we will use a national sample of nursing homes and residents as the comparison group in conjunction with a within-state reference group of non-Initiative facilities. We will present findings from the comparison group analysis and the analytic approaches to evaluating the Initiative effect by using both the national sample comparison group and the within-state reference group. Additionally, we will describe the use of three pre-Initiative years as the baseline period and methods of adjusting for differential trends in hospitalization rates between the Initiative facilities and comparison facilities.